997 Audit Examining the Treatment of Patients Who Developed Post Operative Complications Following Appendicectomy. (19th August 2022) - Garner, J; Butler, J; Evans, T; Ferguson, H
Abstract: Aim: To identify trends in management of patients with post operative complications following appendicectomy in a district general hospital. Method: The coding department identified patients who were admitted with appendicitis in the previous year and those who developed post operative complications. Data was gathered retrospectively from these patients using their online records. Results: Coding identified 270 patients that were admitted between 22/10/20–29/10/21 with appendicitis. 19 patients had post operative complications. 9 had intra-abdominal collections, 5 had wound infections/collections, 3 had an ileus. 15/19 patients with complications underwent imaging, 8 had CT scans and 7 had US scans. Patients waited a mean of 0.4 days between presentation and imaging. Patients waited a mean of 2.2 and median of 0 days between imaging and appendicectomy. 12 patients had complicated appendicitis, 6 had simple appendicitis and 1 had a normal appendix. 16 patients had antibiotics pre and post operatively, 3 did not. The mean length of stay was 5.6 days for patients with complications, compared to a mean length of stay of 3.9 days for all patients with appendicitis. Conclusions: Early identification and management of appendicitis reduces morbidity, and our centre appears to have lower than average complication rates. The patients who did develop complications, were generally imaged and operated on efficiently An area of improvement is ensuring all patients undergoing appendicectomies are given at least one preoperative dose of antibiotics and up to 3–5 days post operatively if complicated as per WSES guidelines. We aim to re-audit this after an education drive within our department.